Investigation Of Copper(I)Thiocyanate (CuSCN) As A Hole Transporting Layer For Perovskite Solar Cells Application - Muhammad Mustafa, Ahmad Nizamuddin; A Subki, A Shamsul Rahimi; Ing, Jia Rong; Saat, Shahrizal; Arith, Faiz; Zainal Abidin, Muhammad Zaimi (Penerbit Akademia Baru, 2021)
Copper(I) Thiocyanate (CuSCN) is an inorganic hole transporting layer (HTL) used in perovskite solar cells (PSC). This material offers higher stability and reliability compared to conventional HTL. In this work, for depositing CuSCN (inorganic compound) we were using spin coating technique. The annealing temperature of CuSCN is varied in order to analyze the structural and electrical characteristics. The structural characteristics are determined by scanning electron microscopy (SEM), Raman spectroscopy and X-ray diffraction (XRD). Meanwhile, the electrical characteristic is measured by the I-V characteristics measurement. SEM images show the material surface features such as crystallinity morphology and density. XRD and Raman spectroscopy are used to confirm the coated surface on the ITO substrate is CuSCN. Besides, the I-V characteristic reveals that the conductivity with respect to annealing temperature. As a result, the optimized annealing temperature of CuSCN is 80 °C and showing conductivity of 62.96 S/m. In conclusion, CuSCN has a significant conductivity, hence suitable for the application as the HTL for perovskite solar cells.